Comparative Research of Isotherm, Kinetic, and Thermodynamic Studies for Neutral Red Adsorption by Activated Carbon Prepared from Apple Peel - Kul, Ali Riza; Koyuncu, Huelya; Turan, Aysenur; Aldemir, Adnan (Springer Int Publ Ag, 2023)
In this study, activated carbon (AC) obtained with apple peel was used for removal of Neutral Red (NR) from aqueous solutions. The characterization of AC was evaluated with the Brunauer-Emmett-Teller (BET), Fourier transform infrared spectra (FTIR), X-ray diffraction (XRD), and scanning electron microscopy/energy-dispersive X-ray spectroscopy (SEM/EDX) analyses. Isotherm, kinetic, and thermodynamic parameters were determined for NR removal with AC. Eighteen isotherm models and eight kinetic models were analyzed for three temperatures and six initial dye concentrations. The experimental data best agree with the Langmuir model among the isotherm models, and the maximum adsorption capacity (q(m)) was calculated 142.857 mg/g at 318 K. It was determined that the pseudo-second-order (PSO) model was the best choice among the kinetic models with the highest correlation coefficients. The removal percentage of NR dye with AC obtained 82.13%, 84.79%, and 87.20% for 120 mg/L initial dye concentration at 298 K, 308 K, and 318 K, respectively. The negative free energy, enthalpy, and entropy values of adsorption obtained - 6386 J/mol, 46280 J/mol, and 165.48 J/mol.K for 20 mg/L NR concentration at 318 K, respectively. The results of this separation process shown spontaneous essence, and workability coinciding with the negative free energy and activation energy was found 13.651 kJ/mol. The assessment of the isotherm, kinetic, and thermodynamic results were evaluated with error functions. The highest correlation coefficient (R-2) values and the lowest sum of squares (SS), sum of the square of error (SE), and mean square of error (MSE) values were determined with Langmuir isotherm and PSO kinetic models. This research showed that AC prepared from biomass can be used effectively for wastewater treatment using adsorption technique.
Keywords: Neutral Red; Activated carbon; Adsorption; Isotherm; Kinetic; Thermodynamic